SMALL AND MEDIUM-SIZED COMPANIES’ SATISFACTION WITH BANKS’ SERVICE QUALITY - Jureviciene, Daiva; Skvarciany, Viktorija (European Scientific Journal, ESJ, 2014)
This paper studies the scientific approaches of customer satisfaction and determinants influencing an overall customer satisfaction. Analyzing the concepts of satisfaction, it was found that the greatest impact on customer satisfaction with commercial banks has the service quality. Also the elements influencing the service quality were identified and investigated. These elements were as follows: understanding the business environment, commuting, flexibility, communication skills, interest in small and medium-sized businesses, speed of decision-making, responding to customer needs, awareness, level of expertise, reliability. After statistical investigation it was found that only understanding the business environment, flexibility, communication skills and level of expertise are statistically significant elements. As a consequence, the regression model of small and medium-sized companies’ satisfaction with commercial banks’ services’ quality was established.